2021
DOI: 10.14710/jphtcr.v4i2.10809
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution in Waters and its Impact on Health and Environment in Indonesia: A Review

Abstract: Introduction: Microplastics have become a pollution problem that has received worldwide attention. Microplastics in the water impact the environment and health, especially in Indonesia, which is the second-largest plastic waste contributor in the world. This literature study aims to determine the distribution of microplastics pollution in waters and its impact on health and the environment in Indonesia.Methods: The literature search on papers from 2010-2021 through Google Scholar, Pubmed, ScienceDirect, and Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Indonesia is one of the countries facing the problem of microplastic contamination [8] [9] based on the Ministry of the Environment of the Republic of Indonesia stating its monitoring that 75% of rivers are heavily polluted from household waste. Apart from that, Indonesia is in second place as the country that produces the most plastic waste in the sea in the world, reaching 187.2 million tonnes after China, which reached 262.9 million tonnes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is one of the countries facing the problem of microplastic contamination [8] [9] based on the Ministry of the Environment of the Republic of Indonesia stating its monitoring that 75% of rivers are heavily polluted from household waste. Apart from that, Indonesia is in second place as the country that produces the most plastic waste in the sea in the world, reaching 187.2 million tonnes after China, which reached 262.9 million tonnes [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the microplastic research was more spread on Java Island (49%) than other Indoensia islands [11]. The sources of microplastics in Indonesia led to domestic waste, tourism, and fishing activities as the primary sources [13]. Those activities were found in Lampung Province as a part of Minapolitan.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the fiber generally comes from river or estuary waters of different sizes. One of many fish with high concentrations of microplastics is Lemuru fish (Basri et al, 2021). FTIR analysis showed that the highest microplastic content in fish species in coastal areas was polyethylene (PE) compared to other polymers (polypropylene (PP), polystyrene (PS), polyethylene terephthalate (PET), polyvinyl chloride (PVC) and polyamide (PA) (Llorca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%